Near Infrared Spectroscopy in Wildlife and Biodiversity. Issue 1 (February 2016) - Vance, Carrie K.; Tolleson, Doug R.; Kinoshita, Kodzue; Rodriguez, Jaime; Foley, William J.
Near infrared (NIR) spectroscopy has been used to answer a wide variety of questions in wildlife and biodiversity research. Whereas agricultural systems and manufacturing seek to limit variation in production systems, wildlife and biodiversity research must embrace it. Variation amongst individuals is the material on which natural selection operates and NIR spectroscopy provides a means to catalogue this variation and to use it in broader ecological and evolutionary analyses and for practical conservation outcomes. In this review we describe how NIR spectroscopy has been applied in wildlife and biodiversity research to obtain data that we could not obtain otherwise. Here we describe a range of applications for which NIR spectroscopy has been applied to questions in taxonomy, physiology, habitat evaluation and population monitoring and highlight new approaches that will allow NIR spectroscopy to be used more widely in wildlife and ecological studies.